Penilaian pencemaran logam berat dalam sedimen di Teluk Jakarta - Edward Edward (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2020)
Contamination and pollution of heavy metals in the bottom sediment can pose serious issues to marine organisms and human health. Jakarta Bay which is located adjacent to the capital city of Indonesia is notorious for its pollution problems. The purpose of this research was to assest the contamination levels of heavy metals Hg, Pb, and Cd in sea-bottom sediments based on an index analysis approach (contamination factors, geo accumulation index, pollution load index). Sediment samples were collected from 31 stations in Jakarta Bay. Heavy metal concentration was measured using Atomic Absorption Spectrophotometer (AAS). The results showed that an average mercury (Hg) concentration ranged from 0.150 to 0.530 g.g-1 with an total average of 0.362 g.g-1, Lead (Pb) from 14.870 to 35.650 g.g-1 with an total average of 21.774 g.g-1, Cadmium (Cd) 0.110-0.280 g.g-1 with an total average of 0.190 g.g-1.The average concentration of Hg, Pb, and Cd is still lower than the sediment quality threshold values set by the Office of the State Minister of Environment of Indonesia 2010. The results of the index analysis showed that the average value of contamination factor (CF) are Hg 0.685, Pb 0.558, and Cd 0.380 respectively (low contamination) and geo accumulation index values are Hg 0.237, Pb -1.655, and Cd 0.069 respectively (unpolluted to moderate polluted). Overall, based on the pollution load index value is -0,511 (PLI 1), sediments in these waters are categorized as not yet polluted by Hg, Pb and Cd. This situation is so necessary to be maintained, that in order for the preservation of marine resources will remain.Keywords:Jakarta Bay, sediment,pollution, heavy metals,assessmentABSTRAKKontaminasi dan pencemaran logam berat pada sedimen dasar dapat menimbulkan masalah yang serius bagi biota laut dan kesehatan manusia. Teluk Jakarta yang terletak berdekatan dengan ibu kota Indonesia terkenal karena masalah pencemarannya yang parah. Tujuan penelitian ini adalah untuk menilai tingkat kontaminasi logam berat Hg, Pb dan Cd dalam sedimen dasar laut berdasarkan pendekatan analisis indeks. Contoh sedimen diambil dari 31 stasiun penelitian di Teluk Jakarta. Kadar logam berat diukur dengan alat Spektrofometer Penyerapan Atom. Hasil penelitian menunjukkan kadar Hg rerata berkisar 0,150-0,530 g. g-1 dengan rerata total 0,362 g. g-1, Timbal (Pb) 14,870-35,650 g. g-1 dengan rerata total 21,774 g. g-1, Kadmium (Cd) 0,110-0,280 g. g-1 dengan rerata total 0,190 g.g-1. Kadar rerata Hg, Pb dan Cd masih lebih rendah dari nilai ambang batas kualitas sedimen yang ditetapkan oleh Kantor Menteri Negara Lingkungan Hidup Indonesia 2010. Hasil analisis indeks menunjukkan nilai rerata faktor kontaminasi (CF) berturut-turut adalah Hg 0,685, Pb 0,352 dan Cd 0,380 (kontaminasi rendah) dan nilai indeks geo akumulasi berturut-turut adalah Hg 0,227, Pb 1,098 dan Cd 0,633 (tidak tercemar sampai tercemar sedang). Secara keseluruhan, berdasarkan nilai indeks beban pencemaran yakni -3.772 (PLI 1), sedimen di perairan ini termasuk kategori belum tercemar oleh Hg, Pb dan Cd. Keadaan ini perlu dipertahankan, agar kelestarian sumberdaya laut tetap terjaga.Kata kunci:Teluk Jakarta, sedimen, pencemaran, logam berat, penilaian